Regular Chinese Green Tea Consumption Is Protective for Diabetic Retinopathy: A Clinic-Based Case-Control Study - Qinghua Ma; Dandan Chen; Hong-Peng Sun; Ning Yan; Yong Xu; Chen-Wei Pan (Journal of Diabetes Research)
Objective. To determine the association between regular Chinese green tea consumption and the risk of diabetic retinopathy (DR) in diabetic patients in China. Methods. 100 DR patients and 100 age-sex-matched diabetic controls without retinopathy were recruited in a clinic-based, case-control study. DR was defined from retinal photographs and detailed information on Chinese green tea consumption of the participants was collected through a face-to-face interview. Results. The crude odds ratio [OR] of Chinese green tea consumption for DR was 0.49 (95% confidence interval: 0.26–0.90). When stratified by sex, the protective effect of Chinese green tea consumption on DR was statistically significant in women (P=0.01) but not in men (P=0.63). After adjusting for age, sex, and other confounders, DR was significantly associated with Chinese green tea consumption (OR = 0.48; P=0.04), higher systolic blood pressure (OR = 1.02; P=0.05), longer duration of diabetes (OR = 1.07; P=0.02), and the presence of family history of diabetes (OR = 2.35; P=0.04). Conclusions. Diabetic patients who had regularly drunk Chinese green tea every week for at least one year in their lives had a DR risk reduction of about 50% compared with those who had not. Regular Chinese green tea consumption may be a novel approach for the prevention of DR.